Knowledge and attitude of key community members towards tuberculosis: mixed method study from BRAC TB control areas in Bangladesh - Paul, Sukanta; Akter, Rahima; Aftab, Afzal; M Khan, Antora; Barua, Mrittika; Islam, Shayla; Islam, Akramul; Husain, Ashaque; Sarker, Malabika (© 2015 BioMed Central Ltd., 2017)
This article was published in BMC Public Health [© 2015 BioMed Central Ltd.] and the definite version is available at: http://bmcpublichealth.biomedcentral.com/articles/10.1186/s12889-015-1390-5